EyePursuitLinks - an Eye-pursuit Based Interface for Web Browsing Using Smart Targets - Carneiro, Alex Torquato Souza; Gonzales, Candy Veronica Tenorio; Morimoto, Carlos Hitoshi (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2023: Proceedings of the 29th Brazilian Symposium on Multimedia and the Web, 2023)
Web accessibility and digital inclusion are still one of the great research challenges in computer science. For people with severe motor disabilities, eye-gaze interaction enables hands-free operation of graphical interfaces. Nonetheless, gaze tracking devices typically require frequent user calibration that weakens the overall user experience and performance. In this paper we propose EyePursuitLinks, an eye-pursuit based technique that allows people with severe motor disabilities to browse the web by following multiple moving targets corresponding to the links they want to follow. The main contribution of this paper is the use of Smart Targets (ST) to select potentially large number of hyperlinks within a relatively small area. We have performed a user experiment with 10 volunteers to evaluate the performance of the Smart Targets selection against conventional pursuit selection mechanism using 4, 8, and 16 simultaneous targets. Our results show that the use of ST is significantly more robust than the conventional method for larger number of targets.